Supply Chain Integration and Business Performance in the Telecommunication Industry in Nigeria - J .U. D Didia; N. Gladson Nwokah (International Journal of Supply Chain Management, 2015)
The purpose of this explanatory research is to evaluate the association between supply chain integration and business performance in the telecommunication industry in Nigeria. This study used a structured questionnaire to elicit responses from respondents from the Telecommunication firms in Nigeria. Returned copies of questionnaire were analyzed using both descriptive and inferential statistics. Descriptive statistics was used to determine the mean and standard deviation of the distribution, while the Spearman rank order correlation co-efficient was used to ascertain the associations between the supply chain integration and the dimensions of business performance in the telecommunication firms in Nigeria. The results of the study reported herein, shows that supply chain integration associates with business performance in the Nigeria Telecommunication firms. It is the recommendation of this paper that managers of Nigerian Telecommunication firms should strengthen their practice of supply chain Integration strategy as a paradigm shift from the isolated functional dependence. The study reported in this paper can be carried out in other industry; and also, in other culture to ascertain whether the same, similar or different outcomes can be achieved.